Teacher Strategies in the Inclusive Learning Process for Early Childhood - Delfianti, Shinta; Hijriati, Hijriati (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Inclusive early childhood education (ECE) is essential for children's character, spiritual, and cognitive development. Its success relies on teachers, instructional strategies, collaboration, and professional training that support non-discriminatory educational practices. This study analyses the inclusive teaching strategies used by ECE teachers at Aceh Flexi School in Banda Aceh. It develops a flexible and responsive learning model based on previous findings for inclusive education. The study employs a qualitative case study approach with purposive sampling. Data were collected through observation, interviews, and documentation, and analysed descriptively through data condensation, presentation, and conclusion drawing. The findings reveal that teachers' strategies in inclusive learning at Aceh Flexi School include planning based on initial assessments, developing Individualised Learning Programs (ILPs), and using concrete media and flexible methods tailored to children's needs. Teachers apply individualised and multisensory approaches during implementation to ensure all children's engagement. Evaluation is conducted contextually, focusing on each child’s learning process and developmental progress. Strong collaboration between teachers, therapists, and parents is a core strength. Despite challenges such as varying student abilities and limited parental awareness, holistic and communicative strategies make inclusive education more effective and meaningful. Conclusion: Inclusive ECE strategies require active teacher involvement in adaptive, collaborative, and contextual planning, implementation, and evaluation to meet individual learners’ needs.